아까시나무 임분의 시계열적 생장 모니터링 및 벌기령 도출 - 김재엽; Jaeyeop Kim; 김소라; Sora Kim; 송정은; Jeongeun Song; 성상민; Sangmin Sung; 임종수; Jongsoo Yim; 손영모; Yeongmo Son (한국산림과학회지, 2022)
본 연구는 5차, 6차, 7차 국가산림조사 자료 중 아까시나무가 우점종인 표본점을 수집하여, 산림조사 차수별, 기후 대별(온대 북부, 온대중부, 온대남부, 난대지역), 해발고별(100 m 단위) 흉고직경, 입목본수, ha당 재적 및 지위지수의 변화를 구명하고자 하였다. 또한 용재로서 사용을 위한 기준인 벌기령을 산정하였다. 그리고 변화 구명은 통계처리 기법 중 분산분석과 Duncan 검정으로서 이행하였다. 흉고직경의 변화를 보면, 당연히 산림조사 차수에 따라 증가하였고, 기후대별로는 온대남부 지역에서 가장 생장이 좋지 않았으며, 해발고별로는 301-400 m 지점에서 가장 생장이 떨어지는 것으로 나타났다. ha당 입목밀도는 산림조사 차수별, 해발고에 따라서 서로 간 차이를 보이지 않았으며, 온대중부 지역에서 밀도가 가장 높고, 온대남부 지역이 가장 낮은 밀도를 보였다. ha당 임분재적은 산림조사 차수에 따라 증가하였고, 온대북부ㆍ온대중부 지역과 온대남부· 난대 지역으로 크게 두 그룹으로 구분되며, 해발고 201-300 m에서 재적생장량이 가장 높았다. 지위지수는 ha당 임분재적 변화와 유사한 결과를 보여 주었다. 그리고 아까시나무의 ha당 재적변화를 알 수 있는 생장량 곡선은 Weibull 함수식으로 추정하였으며, 임분재적은 임령 50-60년에 이를 때 약 200 m3에 달할 것으로 예측되었다. 아까시나무를 밀원 자원이 아닌 용재로 이용하기 위한 기준인 재적수확최대벌기령을 계산한 결과 34년으로 나타났다. The study aim was to investigate changes in the diameter, number of standing trees, stand volume per ha and site index by the forest survey order, climate zone (northern temperate, central temperate, southern temperate, and warm temperate regions), and altitude in 100 m intervals) by collecting samples of Robinia pseudoacacia from the fifth, sixth, and seventh national forest survey datasets. The rotation cutting age, which is a standard used for wood, was calculated. The changes were statistically analyzed by performing ANOVA and the Duncan multiple test. Diameter growth naturally increased according to the forest survey order and was lowest in the southern temperate region by climate zone and lowest at the 301-400 m altitude. The number of standing trees per ha did not change according to the forest survey order and altitude, and the density was highest in the central temperate region and lowest in the southern temperate region. The stand volume per ha increased according to the forest survey order, and the climate zone was divided into two groups: ① northern temperate region and central temperate region, ② southern temperate region and warm temperate region. The stand volume growth was highest at the 201-300 m point. Thesite index showed results similar to the change pattern of the stand volume per ha. The growth curve, which can be seen by the change in stand volume per ha, was estimated by applying theWeibull formula, and the stand volume per ha was estimated to reach approximately 200 m3/ha at 50-60 years. The rotation of the highest production in volume, which is the standard for using trees as wood rather than honey sources, was calculated to be 34 years.